Deteksi Molekuler Ekson 3 Gen Beta Globin pada Pasien Beta Talasemia Mayor di RSUD DR. Soeroto Ngawi menggunakan Metode Polymerase Chain Reaction- Single Strand Conformation Polimorfism - Choirul Huda; Ana Indrayati; Elfahmi Elfahmi (Jurnal Farmasi Indonesia, 2019)
Talasemia is a genetic disease that causes globin chain synthesis disorder, a major component of the hemoglobin molecule. With the synthesis of unbalanced globin chains will decrease the production of red blood cells. This study aims to determine the presence of mutations in exon 2 gene beta globin thalassemia patients using PCR method, where 5 samples in DNA isolation and continued PCR amplification, the amplification result of electrophoresis region 2 beta globin gene Region II is the result of amplification of primary 4 and primer primer reverse 5 with a target of 350 bp, on PCR there is amplification or doubling of the desired DNA sequence based on the primary selection for the reaction, the PCR product of each of these regions which is subsequently performed by SSCP. PCR-SSCP could analysis the mutation in exon 3 beta globin genes. In the PCR-SSCP result, there was no mutation in region 4 exon 3 in five samples but probably there was mutation in another regions.